Fifteen-year follow-up of relapsed indolent non-Hodgkin lymphoma patients vaccinated with tumor-loaded dendritic cells. Issue 6 (14th June 2021) - Fucà, Giovanni; Ambrosini, Margherita; Agnelli, Luca; Brich, Silvia; Sgambelluri, Francesco; Mortarini, Roberta; Pupa, Serenella M; Magni, Michele; Devizzi, Liliana; Matteucci, Paola; Cabras, Antonello; Zappasodi, Roberta; et al.
Abstract : We previously published the results of a pilot study showing that vaccination with tumor-loaded dendritic cells (DCs) induced both T and B cell response and produced clinical benefit in the absence of toxicity in patients with relapsed, indolent non-Hodgkin lymphoma (iNHL). The purpose of the present short report is to provide a 15-year follow-up of our study and to expand the biomarker analysis previously performed. The long-term follow-up highlighted the absence of particular or delayed toxicity and the benefit of active immunization with DCs loaded with autologous, heat-shocked and UV-C treated tumor cells in relapsed iNHL (5-year and 10-year progression-free survival (PFS) rates: 55.6% and 33.3%, respectively; 10-year overall survival (OS) rate: 83.3%). Female patients experienced a better PFS (p=0.016) and a trend towards a better OS (p=0.185) compared with male patients. Of note, we observed a non-negligible fraction of patients (22%) who experienced a long-lasting complete response. In a targeted gene expression profiling of pre-treatment tumor biopsies in 11 patients with available formalin-fixed, paraffin-embedded tissue, we observed that KIT, ATG12, TNFRSF10C, PBK, ITGA2, GATA3, CLU, NCAM1, SYT17 and LTK were differentially expressed in patients with responder versus non-responder tumors. The characterization of peripheral monocytic cells in a subgroup of 14 patients with available baseline blood samples showed a higher frequency of the subset of CD14 ++ CD16 + cells (intermediate monocytes) in patients with responding tumors. Since in patients with relapsed iNHL the available therapeutic options are often incapable of inducing a long-lasting complete remission and can be sometimes characterized by intolerable toxicity, we think that the encouraging results of our long-term follow-up analysis represent a stimulus to further investigate the role of active vaccination in this specific setting and in earlier lines of therapy and to explore novel combinatorial strategies encompassing other innovative immunotherapy agents, such as immune-checkpoint inhibitors.